Cardiorespiratory and muscular responses to simulated upwind sailing exercise in optimist sailors - Callewaert, M.; Boone, J.; Celie, B.; de Clercq, D.; Bourgois, J. G. (Pediatric Exercise Science, 2014)
The aim of this work was to gain more insight into the cardiorespiratory and muscular (m. vastus lateralis) responses to simulated upwind sailing exercise in 10 high-level male and female Optimist sailors (10.8-14.4 years old). Hiking strap load (HSL) and cardiorespiratory variables were measured while exercising on a specially developed Optimist sailing ergometer. Electromyography (EMG) was used to determine mean power frequency (MPF) and root mean square (RMS). Near-infrared spectroscopy was used to measure deoxygenated Hemoglobin and Myoglobin concentration (deoxy[Hb+Mb]) and re-oxygenation. Results indicated that HSL and integrated EMG of the vastus lateralis muscle changed in accordance with the hiking intensity. Cardiore- spiratory response demonstrated an initial significant increase and subsequently steady state in oxygen uptake (VO2), ventilation (VE), and heart rate (HR) up to circa 40% VO2peak, 30% VEpeak and 70% HRpeak respec- tively. At muscle level, results showed that highly trained Optimist sailors manage to stabilize the muscular demand and fatigue development during upwind sailing (after an initial increase). However, approaching the end of the hiking exercise, the MPF decrease, RMS increase, and deoxy[Hb+Mb] increase possibly indicate the onset of muscle fatigue.